DISCLAIMER: This problem is explained properly on my YouTube channel, at the following link: PROBLEM: Analysis of 2x2 Matrices using Cayley-Hamilton Theorem. I suggest you watch this before looking below.

Before I start, let's recall the Cayley-Hamilton Theorem:

**Theorem (Cayley-Hamilton Theorem)** If \(A\) is a square matrix and \(c_A(\lambda) = \det(\lambda I-A)\) is its characteristc polynomial, then (allowing for matrices as the polynomial variable) \(c_A(A) = \bf{0}\), where \(\bf{0}\) is the zero square matrix.

Suppose now that \(A\) is the following 2 x 2 matrix:

\( A = \begin{pmatrix} a & b\\ c & d \end{pmatrix} \)

Note that the trace (denoted by \(t\)) and determinant (denoted by \(\Delta\)) is \( t = a + d \) and \( \Delta = ad-bc \) respectively. Then the characteristic polynomial of \(A\) is:

\( \begin{split} c_{A}(\lambda) &= \det(\lambda I - A) = \det \begin{pmatrix} \lambda - a & -b \\ -c & \lambda - d \end{pmatrix} \\ &= (\lambda - a)(\lambda - d) - bc \\ &= \lambda^2 - t \lambda + \Delta \end{split} \)

Thus, by the Cayley-Hamilton Theorem:

\( A^2 - tA + \Delta = \bf{0}\)

or:

\( A^2 = tA - \Delta\)

What we can see is that \(A^2\) can be expressed in terms of \(A\), \(t\) and \(\Delta\). Can we express \(A^3\) in terms of \(A\), \(t\) and \(\Delta\)? Well, let's compute this:

\( \begin{split} A^3 &= AA^2 = A(tA - \Delta) \\ &= tA^2 - \Delta A = t(tA - \Delta) - \Delta A \\ &= (t^2 - \Delta)A - t\Delta \end{split} \)

So here's two open problems for you:

1) How to express \(A^n\) in terms of \(A\), \(t\) and \(\Delta\)?

2) Can we do something similar for square matrix of arbitrary sizes? How about a 3 x 3 matrix?

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestFor problem 1, here's an outline of an idea that I think might work, though I'm not very sure. Also, I think this method will give the closed form in the form of some cases with conditions imposed on \(t\) and \(\Delta\).

Denote \(x_n=A^n\) and define \(A^0=I\) where \(I\) is the identity matrix of the same order as \(A\). Then we have,

\[x_n=A^n=A^2A^{n-2}=(tA-\Delta)A^{n-2}=tA^{n-1}-\Delta A^{n-2}=tx_{n-1}-\Delta x_{n-2}~\forall~n\geq 2\qquad(1)\]

Since \(t\) and \(\Delta\) only depend on \(A\) which is independent of \(n\), we note that \(t,\Delta\) are independent of \(n\) and hence \((1)\) can be seen as a linear recurrence relation with constant coefficients and we can use the method described here to get a closed form for \(x_n\), i.e., a closed form for \(A^n\) in terms of \(t,\Delta,A\) using the initial values \(x_0=I\) and \(x_1=A\).

I tried working on the case where the auxillary equation for the recurrence has distincts non-zero roots, i.e., when \(\Delta\neq 0\) and \(t^2\neq\Delta\), and let me tell you, the result is not very pretty. We have,

\[A^n = c_1\alpha^n + c_2\beta^n\]

where \(\alpha,\beta=\dfrac{-t\pm\sqrt{t^2-4\Delta}}2\) and \(c_1=\dfrac 1{\beta-\alpha}(\beta I-A)\) and \(c_2=\dfrac 1{\beta-\alpha}(-\alpha I+A)\)

I think there might be a better way to approach the problem but this is all I have right now. Will update the comment if I figure out a better way.

Log in to reply

I guess Problem 1 is almost solved; once you have the linear recurrence, just find the generating function and go from there (I know I'm projecting, and I'm expecting some sort of sh*tstorm!).

Any ideas on Problem 2?

Log in to reply

Essentially yes. What you want is the characteristic polynomial of the matrix which arises from cayley hamilton theorem. Say it has degree \( d \leq n \).

Then, every matrix \( A^k\) can be expressed as \( I, A, A^2, \ldots, a^{d-1} \) by repeated substituting in the characteristic polynomial. You could use the linear recurrence relations to solve for each coefficient if desired.

Log in to reply